Mortal secrets : Freud, Vienna, and the discovery of the modern mind - Tallis, Frank (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2024)
"A chronicle of Vienna's Golden Age and the influence of Sigmund Freud on the modern world by a clinical psychologist whose mystery novels form the basis of PBS's Vienna Blood series. Some cities are like stars. When the conditions are right, they ignite, and burn with such fierce intensity that they outshine every other city on the planet. Vienna was one such city and, at the beginning of the twentieth century, was the birthplace of the modern mind and the way we live today. Long coffee menus and celebrity interviews are Viennese inventions. 'Modern' buildings were appearing in Vienna long before they started appearing in New York and the idea of practical modern home design originated in the work of Viennese architect Adolf Loos. The place, however, where one finds the most indelible and profound impression of Viennese influence is inside your head. How we think about ourselves has been largely determined by Vienna's most celebrated resident, Sigmund Freud. In Mortal Secrets, Frank Tallis brilliantly illuminates Sigmund Freud and his times, taking readers into the mind of one of the most influential thinkers of the twentieth century, chronicling the evolution of psychoanalysis and opening up Freud's life to embrace the Vienna he lived in and the lives of the people he mingled with from Gustav Klimt to Arnold Schönberg, Egon Schiele to Gustav Mahler. Mortal Secrets is a thrilling book about a heady time in one of the world's most beautiful cities and its long shadow that extends through the twentieth century up until the present day"--